2022
DOI: 10.1007/s40121-022-00693-x
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Treatment Options for Severe Fever with Thrombocytopenia Syndrome Infections

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is a tick-borne virus that produces severe fever with thrombocytopenia syndrome (SFTS). It is widespread in Japan, South Korea, and Central and Eastern China. The epidemic has developed rapidly through China in recent years. SFTS cases have been reported in 25 provinces in China, mainly distributed in rural areas in mountainous and hilly areas. The infection has a high case fatality rate and no specific treatments or vaccinations. Therefore, early diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Antiviral therapy in #1 SFTSV. Zhang et al's review ( 40 ) suggested that broad-spectrum antivirals have the potential to be the first line of defense to prevent the progression of the disease, and fapiravir maybe the most promising treatment. The future development of antiviral methods may depend mainly on targeted therapies such as monoclonal antibodies and prevention through vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral therapy in #1 SFTSV. Zhang et al's review ( 40 ) suggested that broad-spectrum antivirals have the potential to be the first line of defense to prevent the progression of the disease, and fapiravir maybe the most promising treatment. The future development of antiviral methods may depend mainly on targeted therapies such as monoclonal antibodies and prevention through vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Blood profile and metabolic panel findings mirror those of HRTV, including thrombocytopenia and elevated liver enzymes [78]. Conservative treatment addressing underlying conditions is often applied, though both ribavirin and favipiravir have shown some potential for treatment in a clinical setting [79]. Additional prospective, randomized trials may help reveal the utility of antiviral treatments-though the importance of early differentiation and diagnosis in the evaluation of various treatment options cannot be understated [79].…”
Section: Clinical Findings Differential Diagnosis Treatment and Progn...mentioning
confidence: 99%
“…Therefore, it is urgent to precisely predict the risk of developing into encephalitis and mortality at the early stage of SFTS. Despite there being no effective therapy for SFTS currently [ 11 ], emerging evidence suggests that some medical interventions, such as calcium channel blockers and favipiravir, might ameliorate the disease progression and reduce the fatality of patients with SFTS [ 12 , 13 ]. Therefore, it is urgent to establish precise prognosis models to predict the fatality of SFTS disease or its association with encephalitis.…”
Section: Introductionmentioning
confidence: 99%